Comparative Assessment of Preoperative versus Postoperative Dexamethasone on Postoperative Complications following Lower Third Molar Surgical Extraction - Hashem M. Al-Shamiri; Maha Shawky; Nermin Hassanein (International Journal of Dentistry)
Aim. To evaluate the effect of preoperative versus postoperative administration of oral Dexamethasone on postoperative complications including pain, edema, and trismus following lower third molar surgery. Methods. 24 patients were divided into two equal groups receiving 8 mg Dexamethasone orally, one group one hour preoperatively and the other group immediately after surgery. Pain was measured using VAS, edema was measured using a graduated tape between 4 fixed points in the face, and the mouth opening was measured using a graduated sliding caliper. Results. In this study pain and trismus records were similar and statistically nonsignificant in both groups. The results had proven that preoperative administration was superior when compared to postoperative administration regarding edema (0.002). Conclusions. Preoperative oral administration of 8 mg Dexamethasone was superior to the postoperative administration of the same dose concerning edema after lower third molar surgery.